Newborn examination practices and congenital anomaly detection in public health facilities in Addis Ababa, Ethiopia: a qualitative exploratory study - Alemu, Merertu Temesgen; Abate, Fikre; Mollenhauer, Courtney; Brewster, Hugh; Habel, Alex; Mulatu, Ermias; Taylor, Sebastian; Eshete, Mekonen (Frontiers in Pediatrics, 2026)
BackgroundCongenital anomalies are a leading cause of infant morbidity and mortality, particularly in low-resource settings. Early detection through standardized newborn examinations is critical but remains underexplored in Ethiopia.ObjectiveThis qualitative study systematically assesses neonatal examination practices in major public hospitals in Addis Ababa, Ethiopia, identifying gaps and proposing recommendations for standardized protocols.MethodsWe conducted twelve key informant interviews from November 2024 to January 2025 with pediatricians, obstetrician-gynecologists, and midwives from four large public hospitals using purposive sampling based on role and neonatal care experience. Interviews were transcribed verbatim and analyzed thematically following Braun & Clarke's framework. Coding was performed by two researchers; discrepancies were resolved by consensus. Trustworthiness was enhanced through member checking, peer debriefing, triangulation, and an audit trail.ResultsExamination practices are fragmented, with inconsistent use of structured checklists and inadequate documentation. Training gaps among clinicians and non-physician staff were evident. There is strong interest in adopting checklist-based approaches to improve anomaly detection.ConclusionsThe findings highlight critical gaps in neonatal examination and documentation practices across the study sites. Developing a national checklist, comprehensive training programs, and mandatory protocols could strengthen early detection and management of congenital anomalies.